Let's solve the equation step-by-step.
The equation you provided is:
\[ 20x - 5(6x + 15) = -45. \]
First, distribute the \(-5\) across the expression inside the parentheses:
\[ 20x - 5 \cdot 6x - 5 \cdot 15 = -45. \]
This simplifies to:
\[ 20x - 30x - 75 = -45. \]
Next, combine the \(x\) terms:
\[ (20x - 30x) - 75 = -45 \] \[ -10x - 75 = -45. \]
Now, add \(75\) to both sides to isolate the term with \(x\):
\[ -10x = -45 + 75 \] \[ -10x = 30. \]
Now, divide both sides by \(-10\):
\[ x = \frac{30}{-10} \] \[ x = -3. \]
Therefore, the solution is:
\[ \boxed{-3}. \]